2022
DOI: 10.1097/md.0000000000030094
|View full text |Cite
|
Sign up to set email alerts
|

Response to treatment with an ALK-TKI in a patient with advanced lung adenocarcinoma with concurrent ALK fusion and high PD-L1 expression: A case report

Abstract: Rationale: Previous studies have shown that PD-L1 TPS ≥50% in lung cancer rarely overlaps with driver oncogenes such as epidermal growth factor receptor and anaplastic lymphoma kinase (ALK). The initial gene detection of the patient in this study showed ALK fusion combined with high expression of PD-L1. We explored the treatment options for this patient. Patient concerns: A 34-year-old woman presented for the first time with “repeated fever and cough for 20 days.” The patient denied any underlying medical hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Another study reported that the administration of ensartinib and dabrafenib for the BRAF V600E mutation detected post-alectinib in EML4-ALK–rearranged lung cancer; however, the treatment was discontinued owing to severe adverse events. 6 Further research is needed to address BRAF V600E as a resistance mechanism to ALK TKI. In addition, most studies focused on EML4-ALK, and whether they can be applied to rare variants of ALK-rearranged lung cancers, including HIP1-ALK, needs to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the administration of ensartinib and dabrafenib for the BRAF V600E mutation detected post-alectinib in EML4-ALK–rearranged lung cancer; however, the treatment was discontinued owing to severe adverse events. 6 Further research is needed to address BRAF V600E as a resistance mechanism to ALK TKI. In addition, most studies focused on EML4-ALK, and whether they can be applied to rare variants of ALK-rearranged lung cancers, including HIP1-ALK, needs to be verified.…”
Section: Discussionmentioning
confidence: 99%